Preliminary finding on the switching control algorithm for the stabilization of the DC-DC Zeta converter. - Sarkawi, Hafez; Yoshito, Ohta; Paolo, Rapisarda (2018)
In this paper, we propose a hybrid control algorithm for the stabilization of a dc-dc zeta converter. We derive a switching control law based on a control Lyapunov function candidate to navigate the states to the operating point. The effectiveness of the proposed method is illustrated with simulation results.